1991
DOI: 10.1254/jjp.55.339
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyl radical participation in the in vitro effects of Gram-negative endotoxin on cardiac sarcolemmal Na,K-ATPase activity.

Abstract: ABSTRACT-The effect of in vitro exposure of sarcolemmal membrane (SL) vesicles to Gram-negative endotoxin lipopolysaccharides (LPS) was studied. LPS decreased the Na,K-ATPase activity of SL vesicles; this effect was inhibited by hydroxyl radical (' OH) scavengers such as dimethylthiourea and dimethyl sulfoxide, but not by super oxide dismutase, a scavenger of superoxide anion radicals or by the hydrogen perox ide scavenger catalase. ESR spin-trapping with 5,5-dimethyl-l-pyrroline N-oxide veri fied the generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…Physiologically, superoxide becomes hydrogen peroxide via superoxide dismutase (SOD) (53), which is then inactivated by catalase and becomes H 2 O and O 2 . However, robust ROS generation beyond this catalytic process generates excessive hydroxyl radicals, which are very unstable but have a high potential to damage cellular structures, enzymes, or channel proteins on the cellular membrane (200). These events, together with activation of inflammatory cascades and facilitation of bioactive autacoids, such as cytokines or catecholamines, make cells more susceptible to death (Fig.…”
mentioning
confidence: 99%
“…Physiologically, superoxide becomes hydrogen peroxide via superoxide dismutase (SOD) (53), which is then inactivated by catalase and becomes H 2 O and O 2 . However, robust ROS generation beyond this catalytic process generates excessive hydroxyl radicals, which are very unstable but have a high potential to damage cellular structures, enzymes, or channel proteins on the cellular membrane (200). These events, together with activation of inflammatory cascades and facilitation of bioactive autacoids, such as cytokines or catecholamines, make cells more susceptible to death (Fig.…”
mentioning
confidence: 99%
“…Hidroksil radikali dayanıklı değildir, hücresel yapı-larda, enzimlerde ya da hücre zarındaki kanal proteinlerinde zedelenmeye neden olur. 46 Bu olaylar sonucunda hücreler reperfüzyon başlar başlamaz inflamatuar kaskadın etkinleşmesi ve sitokinler ile katekolaminler gibi biyoaktif molekül-lerin salıverilmesi ile hücresel ölüme ya da miyokardiyal kasılma işlev bozukluğuna daha duyarlı duruma gelir. 47 48 …”
Section: Mi̇yokardi̇yal İskemi̇/reperfüzyon Zedelenmesi̇unclassified
“…In the ischemic or reperfused condition, xanthine hydroxylase changes xanthine oxidase because xanthine oxidase is activated by protease sensitive to Ca 2+ accumulation. Free radicals attack the cellular membrane, and causes cellular damages via inactivation of membrane enzymes, pump and proteins, such as Na + /K + ATPase, Ca 2+ channels and ecto-5′-nucleotidase [15,16]. Gross et al reported that myocardial contractile dysfunction produced by 15 min of ischemia and 3 h of reperfusion is restored by superoxide dismutase [17].…”
Section: Free Radicalsmentioning
confidence: 99%